Organizational image the case of the Locsin dance workshop - Medrano, Rochelle P.
Constituents tend to equate a good organizational image to the number of clients an organization caters to. This misconception becomes projected onto the public, which may think that an organization's large membership is a wide acceptance and can market the organization as one that offers good services and/or products. In this study of the Locsin Dance Workshop's (LDW) organizational image, the study examined how a formal organization can achieved longevity and a good reputation without resorting to the usual methods of operation used by a formal organizations particularly a dance schools. LDW is unique for its non-use of a written syllabus since its establishment. It relies on a steady stream of verbal communication to rely to its students and employees important information like the school's goals and objectives. And while other profitable organization invest in advertising and public relations, LDW under A. Locsin has been using a different approach to advertising. The concept was derived from Fombrun's Reputation framework. The variables: unique needs, motivations, and attitudes as well as the goals and objectives of the constituents and the organization were determined. The first three variables consisted the internal constituents' perceptions. Its coherence with the latter comprised the over-all projected image of the organization. Using Xsight, the transcribed data was further clustered and analyzed. Results showed that despite the lack of syllabus, LDW managed to make its constituents adhere to its goals and objectives b utilizing the family system. The family system which is often used in large-scale organization was helpful in the efficiency of the employees in the workplace. Though LDW was considered formal, its way of instilling its implicit goals and objectives were best attributed through informal ways such as talking to the students before and after the class proper. LDW's image as perceived by its constituents is equivalent to its current artistic director Agnes D. Locsin?s stature and standards which is a company of disciplined and exemplary performers. Also, the protegees of the LDW, who are making their own name in the industry, also contributed to its image by being publicized in mass media. The results revealed that Locsin Dance Workshop is an organization that serves dance enthusiasts and lovers of all ages a venue to gather, explore, create, and share one's artistic dance styles, and an organization which maintains utmost standards and creates a well-disciplined, value-laden and committed family of performers who aim for excellence and perfection in performance.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication